Nota técnica 1: Transmisión eléctrica y la "ley corta": una nota sobre riesgo y la tasa de descuento " - Galetovic, Alexander (Estudios de Economía, 2016)
This paper studies the determinant of the appropriate rate to fix transmissiontolls. I develop a simple model that allows to decompose it in the sum of therisk-free rate and a risk premium. There are two general principles with vhichthe rate should conform: (a) it should vary pari passu with the risk-free rate (b)it should compensate the transmission company for: (i) the “risk of regulatoryopportunism”; (ii) the nondiversifiable risk imposed to the transmission companyby the price-fixing rule; (iii) and also add a liquidity premium. Legislationpresently discussed in congress, however, would grant a fixed 10% real rate tothe transmission company. Approximating the risk-free rate by the rate paid bya 20-year b ond issued by the Central Bank (PRC) I use the model to estimatethe level of risk that justifies a rate of exactly 10%. Finally, I propose a methodto regulate transmission fees that would eliminate most revenue risk and wouldavoid a need to fix a regulated rate.